2021
DOI: 10.3390/nu13061970
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to BPA: The Effects on Hepatic Lipid Metabolism in Male and Female Rat Fetuses

Abstract: Bisphenol A (BPA) is an organic chemical compound widely used for manufacturing plastics. BPA exposure originates principally from the diet, but it can also originate from dermal contact. In over 90% of individuals, including pregnant women, BPA is detectable in several body fluids. The effects of this exposure on the fetus are under active investigation in several research laboratories. The aim of our work was to study the impact of prenatal exposure to BPA in the liver of rat fetuses from a sex-dependent poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 65 publications
(89 reference statements)
0
13
0
Order By: Relevance
“…This lipid accumulation was associated with hyperinsulinemia and the disruption of genes involved in hepatic lipogenesis and cholesterogenesis [61]. These effects on hepatic lipid metabolism were confirmed by many studies that followed, whether they studied exposures in adults or in perinatal mice [59,60,63,64].…”
Section: Effect Of Bpa On the Livermentioning
confidence: 79%
“…This lipid accumulation was associated with hyperinsulinemia and the disruption of genes involved in hepatic lipogenesis and cholesterogenesis [61]. These effects on hepatic lipid metabolism were confirmed by many studies that followed, whether they studied exposures in adults or in perinatal mice [59,60,63,64].…”
Section: Effect Of Bpa On the Livermentioning
confidence: 79%
“…Noteworthily, the urinary concentrations of BPA and phthalate metabolites in our study were far below the reference HBM values for the general population estimated by biomonitoring data. However, some recent studies in rat fetuses [69,70] have shown that maternal exposure to very low doses of BPA (2.5 µg/kg/day) was able to alter hepatic lipid metabolism and metabolic pathways important for the proper development and functioning of the brain. Furthermore, other studies [71,72] have shown that gestational exposure to BPA at low doses was able to cause cognitive deficits and influence the development of circadian centers in the offspring of rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Tonini et al to examine the impact of prenatal exposure to low-dose BPA (2.5 µg/kg/day) on the livers of SD rat foetuses showed that BPA had no effect on TG or total, LDL, or HDL cholesterol in the serum samples of mother rats, and there was no effect on hepatic TG or total cholesterol content in foetal rats [51]. In contrast, C57BL/6J mice exposed to a low dose of BPA (5 µg/kg/day) showed that low gestational BPA exposure significantly increased BW at 13, 14, 20, and 22 weeks and caused a significant decrease in hepatic TG content.…”
Section: High and Low Doses Of Developmental Bpa Exposure And Lipid P...mentioning
confidence: 99%